2003
DOI: 10.1345/aph.1c037
|View full text |Cite
|
Sign up to set email alerts
|

Increased Vitamin B12 Requirement Associated with Chronic Acid Suppression Therapy

Abstract: Initiation of vitamin B(12) supplementation was associated with chronic gastric acid suppression therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 12 publications
0
39
0
1
Order By: Relevance
“…The mechanism of the reduced vitamin B 12 levels in these patients may have been primarily related to sustained achlorhydria producing a reduction in acid-mediated extraction of protein-bound cobalamin [45,46]. In past studies, investigators have reported slight reductions in median serum vitamin B 12 levels; however, the patients enrolled were predominantly elderly and/or those with Zollinger-Ellison syndrome who received high-dose PPI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of the reduced vitamin B 12 levels in these patients may have been primarily related to sustained achlorhydria producing a reduction in acid-mediated extraction of protein-bound cobalamin [45,46]. In past studies, investigators have reported slight reductions in median serum vitamin B 12 levels; however, the patients enrolled were predominantly elderly and/or those with Zollinger-Ellison syndrome who received high-dose PPI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Two older case control studies which also deal with this subject are included in Table 1 [22,41]. In a case control study in 2004 (Table 1)[22] in a geriatric population(≥65 years) the usage of H2R/PPIs and a number of other variables were compared in 53 patients with vitamin B12 deficiency to 212 controls (matched for age, gender, multivitamin use, frequency of Helicobacter pylori infection).…”
Section: Long-term Use Of Ppis and Effects On Vitamin B12(vb12) Amentioning
confidence: 99%
“…Defi nitions of vitamin B 12 defi ciency and use of acid suppression were limited in this analysis. Other retrospective series have linked acid suppression use with greater cobalamin supplementation by primary care physicians [ 29 ]. Additional data on this topic are limited to case reports and physiologic experiments [ 24 ].…”
Section: Cobalamin Malabsorptionmentioning
confidence: 99%